THE INTERNATIONAL FRIENDLY TIE COOPERATION BETWEEN SPECIAL REGION YOGYAKARTA (DIY), REUBLIC OF INDONESIA AND PROVINCE OF GANGWON, REPUBLIC OF KOREA 2009-2014 - Guruh Mahendra Jati Gunawan (HI 16 UMY 053, 2016)
*53 This article is about an international cooperation proposed by provincial government of Gangwon, Republic of Korea to regional government of Special Region of Yogyakarta (DIY), Republic of Indoensia in 2008. The regional government of DIY by Governor Sri Sultan Hamengku Buwono X signed the MoU in September 7th, 2009. There are many aspects cooperated, like health, education, cultural, social and others. This is analyzing the reason behind DIY agreed the cooperation offered by Gangwon. Rational Choice theory becomes the reference in analyzing case. Keywords: paradiplomacy, rational choice, interest